Production of highly charged ions inside a cryogenic Penning trap by electron-impact ionisation - Kanika; Krishnan, Arya; Klimes, Jeffrey W.; Reich, Bianca; Anjum, K. K.; Baus, P.; Birkl, G.; Quint, Wolfgang; Vogel, Manuel (Journal of physics. B, Atomic, molecular and optical physics, 2023)
We have built and operated a cryogenic Penning trap arrangement that allows for the efficient production, selection, and long-term storage of highly charged atomic ions. In close similarity to an electron-beam ion trap it works by electron-impact ionisation of atoms inside a dedicated confinement region. The electrons are produced by field emission at liquid-helium temperature and are subsequently accelerated to the keV energy range. The electron beam is reflected through the trap multiple times to increase the ionisation efficiency. We show a characterisation of the system and measurements with argon and tungsten ions up to Ar16+ and W27+, respectively.